Copper-Mediated Direct Sulfenylation of 4-Hydroxyquinolinones and 4-Hydroxypyridones with Aryl Thiols via a C−H Functionalization Process - Guo, Tao; Wang, Hongyan (Synlett, 2017)
An efficient approach for the direct sulfanylation of 4-hydroxyquinolinones and 4-hydroxypyridones with aryl thiols in the presence of CuI/DMSO has been developed. The substrate scope is broad, allowing facile synthesis of a range of structurally diverse 3-sulfanyl-4-hydroxyquinolinones and 3-sulfanyl-4-hydroxypyridones in good efficiency.
Keywords: sulfanylation; C–H functionalization; quinolinones; pyridones; C–S bond